Rational Goals for the Urban Environment: A Swedish Example - Bjornberg, Karin Edvardsson (European planning studies, 2009)
In Sweden, the government's aim to create sustainable urban environments is expressed through the environmental quality objective "A good built environment". The objective embraces seven sub-goals and is designed to guide central, regional and local authorities' planning towards urban sustainability. However, for objectives concerning the urban environment, such as the Swedish objective "A good built environment", to form a solid basis for decision-making, two types of rationality (functionality) conditions ought to be met. First, the objectives should guide and motivate those who are responsible for their implementation. This is applicable when the goals satisfy the criteria of precision, evaluability, approachability and motivity. Second, when the goals are parts of larger goal systems, the goal systems should be coherent. Using the objective "A good built environment" as an empirical basis, this article gives a few examples of how environmental goals can fail to guide and motivate action towards improved urban sustainability.